Molecular characterization of bat HBV and identification of HDV co-infection in Yunnan, China - Kui, Yushan; Wang, Jiale; Ning, Yuting; Hou, Yutong; Deng, Lulu; Wang, Binghui; Li, Wen; Xia, Xueshan (Frontiers in Microbiology, 2026)
BackgroundBats are natural reservoirs for Orthohepadnaviruses, but the diversity and evolution of bat hepatitis B viruses (BtHBVs) and their co-infection with bat hepatitis D virus (BtHDV) in China remain poorly understood.MethodsIn a molecular survey of bats from Yunnan Province, we detected BtHBV in 36.86% (129/350) of the samples, showing a notably high prevalence in Hipposideros pomona (41.75%). BtHDV co-infection was observed in 1.14% of BtHBV-positive bats.ResultsGenomic analysis of 18 BtHBV isolates revealed that all belong to the bat-specific Orthohepadnavirus Lineage V (BtHBV-7), yet exhibit measurable genetic divergence. We also characterized a highly divergent bat HDV strain, BtHDV-YNNJ49, which clusters within a distinct bat-associated deltavirus lineage but displays substantial genetic divergence from its closest relative, underscoring diversity within this lineage.ConclusionsCollectively, our findings suggest that bats in Yunnan, particularly H. pomona, may act as natural hosts for both BtHBV and BtHDV. The identification of this divergent BtHDV strain expands our understanding of the genetic diversity and evolution of deltaviruses.